Evaluation De La Performance Globale Des C9;tablissements De Microfinance C0; Partir Du Balanced Scorecard: Une C9;tude Empirique En Contexte Camerounais (Global Journal of Management and Business Research, 2019)
The objective of this paper is to evaluate the overall performance of Microfinance Institutions EMFs in Cameroon from the Balanced Scorecard BSc To achieve this goal exploratory interviews with 10 EMFs followed by a confirmatory survey of 88 EMFs were conducted The main results resulting from the construction of the overall performance index and the multiple linear regression are as follows 1 the overall performance quality index depends on 2 193 of the financial dimension and 97 812 of the non-financial dimension 2 the sample EMFs have a low overall performance index 41 7 compared to the average out of 88 EMFs only 25 have a higher overall performance quality index at 50 3 there is a positive and significant relationship between two non-financial performance areas customer focus and innovation and organizational learning and the financial performance axis in the context of the BSc The study recommends the use of BSc by EMFs as they need to balance financial and non-financial performance to ensure their survival in a competitive market while meeting their social purpose
Keywords: global performance assessment; balanced scorecard (BSc); EMF